Efeitos da suplementação de suco de uva sobre estresse oxidativo, inflamação, imunocompetência, desgaste muscular e desempenho de corredores recreacionais - Toscano, Leydiane Tavares (2015)
The use of sports supplements is something already well established in the sport, however recent years have been marked by the discovery of foods that demonstrate ergogenic activity similar to that of sports supplements. Several of these foods show up able to minimize oxidative stress, inflammation and muscle injury induced by intense training. The purple grapes and their derivatives have a particular antioxidant action and anti-inflammatory due to their composition rich in polyphenols, so that has been demonstrated substantial capacity to improve cardiometabolic parameters in hypertensive, diabetic, neurodegenerative and liver diseases. But yet few studies that confirmed the ergogenic capacity of grape juice in athletes. In this context, the present study aimed to investigate the effects of the integral purple grape juice supplementation on oxidative stress, inflammation, immune response, muscle injury and performance in recreational runners. Therefore an experimental study, randomized and controlled was conducted with 28 recreational runners. Two groups were configured: grape juice (GJG; n= 15; 42,7±8,1 anos) who ingested 10 ml/ kg/ day of integral purple grape juice and control group (GC, n= 13; 36,3±8,1 anos) consumed isocaloric carbohydrate beverage, isoglicidic and isovolumetric daily for 28 days. The parameters evaluated were total antioxidant capacity - TAC, vitamins A and E, uric acid and malondialdehyde-MDA (oxidative stress); alpha-1- acid glycoprotein - AGP and high-sensitivity C-reactive protein – CRP-hs (inflammation); leukocytes, neutrophils, lymphocytes and monocytes (immune response); creatine kinase - CK and lactate dehydrogenase - LDH (muscle injury); and exhaustion test, anaerobic threshold and aerobic capacity (performance). Additionally we assessed food intake and body composition; training loads in the season; psychometric behavioral and sleep; cardiac autonomic modulation; liver and kidney enzymes; glucose and lipid profile; plasma nitrite. The statistical analysis showed that GJG increased in total antioxidant capacity (22.5±5.5 vs. 31.2±12.3; p= 0.009), vitamin A (35.5±3.2 vs 39.7±4.0; p= 0.010) and uric acid (3.9±1.6 vs. 5.0±1.1; p= 0.005), when compared the pre and post intervention moments. MDA and vitamin E the values remained unchanged in both groups. The inflammatory marker AGP significantly decreased in GJG (77.2±17.5 vs 64.2±16.8; p= 0.006), but the same not occurred in the CG (64.9±15.8 vs 62.8±19.5; p = 0.480). The run time to exhaustion significantly improved in GJG in 15.3% (89.1±49.9 vs 101.9±56.0; p= 0.002), while GC showed a slight decrease of 2.2% (69.0±34.0 vs 68.2±33.2; p= 0.880). The anaerobic threshold increased 3.6% to GJG (10.6±2.3 vs 11.0±2.4; p= 0.510), while CG decreased 1.6% (11.8±2.1 vs 11.6 ± 2.8; p= 0.820), both descriptively, no significant changes. For aerobic capacity both groups showed discrete increases, but not significant (PGJ: 2.2% vs GC: 2.3%). Immunocompetence and injure muscle markers remained unchanged in both groups. Based on the results we can conclude that the intake of 10 ml/ kg/ day of integral purple grape juice for 28 days have ergogenic capacity to promote improved physical performance, accompanied by increase in antioxidant activity and possible reduced systemic inflammation.